Managerial ownership and firm performance in German small and medium-sized enterprises - Elisabeth Mueller; Alexandra Spitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
We analyze the relationship between managerial ownership and company performance, testing the incentive and entrenchment hypothesis. Differently from previous literature, we focus on small and medium-sized private enterprises which constitute an important part of the German economy. We use a panel of 356 companies in the German business-related service sector for the years 1997-2000. Our findings are that performance, measured by survey-based profit information, is increasing in managerial ownership up to around 40 percent. We do not find a significant entrenchment effect, possibly because at levels at which managers could become entrenched, they already bear a large proportion of the costs and have therefore an incentive to maximize company value.
Keywords: G32; 330; company performance; managerial ownership; corporate governance; small and medium-sized enterprises; Eigentümerstruktur; Corporate Governance; Führungskräfte; Klein- und Mittelunternehmen; Unternehmensentwicklung; Agency Theory; Schätzung; Unternehmensdienstleistung; Deutschland